Evaluation of a novel oral mucosa in vitro implantation model for analysis of molecular interactions with dental abutment surfaces. (12th March 2019) - Roffel, Sanne; Wu, Gang; Nedeljkovic, Ivana; Meyer, Michael; Razafiarison, Tojo; Gibbs, Susan
Abstract: Background: Abutment surfaces are being designed to promote gingival soft tissue attachment and integration. This forms a seal around prosthetics and consequently ensures long‐term implant survival. New scalable and reproducible models are necessary to evaluate and quantify the performance of these surfaces. Purpose: To evaluate a novel implantation model by histomorphometric and immunohistochemical characterization of the interactions between human oral gingival tissue and titanium abutments with either novel anodized or conventional machined surface. Materials and Methods: Abutments were inserted into an organotypic reconstructed human gingiva (RHG) model consisting of differentiated gingival epithelium cells on a fibroblast populated lamina propria hydrogel following a tissue punch. Epithelial attachment, down‐growth along the abutment surface, and phenotype were assessed via histomorphology, scanning electron microscopy, and immunohistochemistry 10 days after implantation. Results: The down‐growing epithelium transitioned from a gingival margin to a sulcular and junctional epithelium. The sulcus depth and junctional epithelial length were similar to previously reported pre‐clinical and clinical lengths. A collagen IV/laminin 5 basement membrane formed between the epithelium and the underlying connective tissue. The RHG expanded in thickness approximately 2‐fold at the abutment surface. The model allowed the evaluation of protein expression of adhering soft tissue cells for both tested abutments. Conclusions: The RHG model is the first in vitro 3D model to enable the assessment of not only human epithelial tissue attachment to dental abutments but also the expression of protein markers involved in soft tissue attachment and integration. The two abutments showed no noticeable difference in epithelial attachment.